Investigating the impact of habitat fragmentation on woodland caribou (Rangifer tarandus) in British Columbia ... - Armour, Claire (Borealis, 2021)
The purpose of this project was to map varying qualities of woodland caribou habitat in BC and quantify fragmentation of different habitat classes between 1985 and 2018. Woodland caribou populations in British Columbia are in steep decline despite extensive intervention efforts by the BC and Canadian Governments. The main drivers behind woodland caribou decline are habitat loss and increased predation. Caribou rely on large, contiguous tracts of mature forest to forage for lichens in the winter, raise their young in the spring, and as protection from predation. Disturbances such as timber harvests, wildfires, and human development fragment these patches, and the young forests and open areas left behind draw deer and moose to the area, exposing caribou to predation. Linear features such as roads, power lines, pipelines, and recreational trails create additional corridors which are used by predators to more easily access caribou herds. By measuring forest fragmentation in caribou herd ranges using landscape ...